SISTEM PENDUKUNG KEPUTUSAN KLASIFIKASI KELUARGA MISKIN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) SEBAGAI ACUAN PENERIMA BANTUAN DANA PEMERINTAH (STUDI KASUS: PEMERINTAH DESA TAMANMARTANI, SLEMAN) - Uning Lestari; Muhammad Targiono (Jurnal TAM (Technology Acceptance Model), 2017)
Various types of government programs in poverty alleviation efforts have been widely implemented, but the assistance that reached the hands of the people has not been in accordance with what is expected. One reason is that the determination of the status of poor families as beneficiaries has not been optimal, so that in providing poverty assistance has not been well targeted. Application Development Decision Support System Determination of Poor Family is made by the method used in determining the decision is the method of Simple Additive Weighting (SAW). The results of the assessment conducted by the system are given poverty status such as Very Poor, Poor, Vulnerable Poor and Not Poor. SAW method is chosen because it can determine the weight value for each attribute, then proceed with the ranking process that will select the best alternative from a number of alternatives, in this case the alternatives referred to are families categorized as poor families based on the criteria specified. With the ranking process, the assessment will be more precise because it is based on predetermined criteria and weights, so it will get more accurate results for anyone who is categorized as poor. These results can then form the basis for the TPK (Poverty Reduction Team) team of Tamanmartani villages to determine which families are entitled to receive government funding so that the distribution of aid is targeted.